REASSESSMENT OF THE «OPTIMUM CURRENCY AREA» THEORY IN THE EUROPEAN UNION - LYPKO, Nazarii (Journal of European Economy, 2023)
The article offers a reassessment of the optimal currency area in the European Union and elaborates on the prospects for its expansion in the modern economic conditions. The assessment builds on the example of Central and Eastern European countries that have joined the euro zone in the recent years. The aim of the study is to compare the performance of the euro-zone countries with that of the non-euro-zone countries in order to determine whether the implementation of the common currency and centralized monetary policy helps to protect national economies from external shocks (balance-of-payments crises) better than keeping national currencies and pursuing independent monetary policy. This would, in turn, help to determine whether the optimum currency area in the European Union is still in existence today and whether it has potential to expand and generate benefits for its future members. The findings of the study prove that the euro zone remains to be an optimum currency area in the given borders with a potential for further expansion. JEL: F36, F45.